(untitled) (Journal of Geography and Environmental Management, 2025)
This paper provides a detailed analysis of key issues in flood risk assessment and management in the Republic of Kazakhstan, where water-related emergencies remain one of the most pressing natural hazards. Particular attention is paid to the specifics of the spring period, when snowmelt, river blockages and sharp temperature fluctuations create the conditions for large-scale flooding. The main causes of flooding are considered, including heavy rains, terrain features, anthropogenic factors, and accidents at hydraulic structures that exacerbate the vulnerability of territories. The study presents modern approaches to risk assessment: hydrological modelling, analysis of long-term observations, and methods for mapping areas of potential flooding. It emphasizes the need for a comprehensive approach that combines engineering solutions, environmental protection measures, improvement of monitoring and early warning systems, and increased preparedness and awareness among the population. In addition, the study highlights the challenges associated with climate change, the deterioration of hydraulic infrastructure, and the complexities of interregional and transboundary water management. The results of the study demonstrate the importance of integrating scientific methods into water risk management practices to increase regional resilience and minimize potential damage.